TINJAUAN KELAYAKAN TEKNIS PENGEMBANGAN KAWASAN PELABUHAN GORONTALO DENGAN MODIFIKASI LINGKUNGAN (REKLAMASI) - Hinelo , Darwis (Jurnal Entropi, 2009)
Port of Gorontalo is one of the existing modes of transportation in the province of Gorontalo, precisely in the city of Gorontalo. Port River estuary, located in almost every year Bone experiencing sedimentation by sediment from the upstream river Bone. Another thing that becomes a problem in development is the port area which is dominated by hills / cliffs, so that alternatives can be done is by modifying the environment or otherwise known as reclamation. Therefore the aim of this study was to identify the condition of the port area of Gorontalo and analyze the technical feasibility of the location that will be reclaimed to do with the development of Port of Gorontalo. The method used in this study were: 1) Methods of field research, which is done by conducting direct observation at the location (primary data) and laboratory testing to determine physical condition. 2) library research methods, the method of data collection by collecting supporting data obtained from the research, the results of studies and data from agencies associated with this research. Results showed that technically feasible land is reclaimed land on the left side in the direction of flow or in the eastern part of the harbor / estuary Bone of 36 900 m2 or 3.69 ha, the volume of embankment needed to reach 369 000, - m3. Embankment material utilizing pieces of the hill which is also useful to facilitate access to ferry ports.